Hubungan Pengetahuan dengan Sikap Ibu Hamil Tentang Pemanfaatan Buku KIA di Puskesmas Buleleng I - Indrayani Indrayani; Regina Tedjasulaksana; Made Widhi Gunapria Darmapatni (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
The KIA Handbook is a health record book containing maternal and child health records as well as various information on how to maintain and care for maternal and child health. In fact, utilization for pregnant women is still low. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women about the use of KIA Handbook at the Buleleng I Public Health Center. The study design used a cross sectional study. The research sample was pregnant women, totaling 73 people. The data collection instrument was in the form of a questionnaire regarding knowledge and attitudes about the use of KIA Handbook. The data were analyzed by the Kendall tau test b. The results showed that 43 pregnant women (58.9%) had a good level of knowledge aboutÂ  use of KIA Handbook. A total of 50 pregnant women (68.5%) had a positive attitude towards the use of KIA Handbook. The results of the bivariate analysis using the Kendall tau b test and the p value = 0.000. This means that there is a relationship between knowledge and attitudes of pregnant women about the use of KIA Handbook at the Buleleng I Public Health Center. The results of this study are expected that health workers always inform mothers about the use of KIA Handbook.